2010
DOI: 10.1007/dcr.0b013e3181ce677a
|View full text |Cite
|
Sign up to set email alerts
|

Single-Access Laparoscopic Colectomy With a Novel Multiport Device in Sigmoid Colectomy for Colon Cancer

Abstract: Single-access laparoscopic sigmoidectomy seems to be feasible and safe when performed by experienced laparoscopic surgeons who are familiar with the unique principles of this procedure. Additional experience and continued investigations are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…The technique has been employed successfully for a number of colorectal procedures, including right hemicolectomy [2,4,6,8,9,[20][21][22][23][24][25], total colectomy [26][27][28], proctocolectomy with ileal pouch anal anastomosis [28,29], and left colectomy [2,25,30]. Several case reports and series have been published involving use of the SILC technique for sigmoid resection [3,7,[31][32][33][34][35][36][37][38], the largest of which included 10 consecutive patients who underwent resection for recurrent diverticulitis [38]. These reports concluded that SILC was safe and feasible without increased operative time, risk of complication, or prolonged hospitalization when performed by an experienced laparoscopic surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…The technique has been employed successfully for a number of colorectal procedures, including right hemicolectomy [2,4,6,8,9,[20][21][22][23][24][25], total colectomy [26][27][28], proctocolectomy with ileal pouch anal anastomosis [28,29], and left colectomy [2,25,30]. Several case reports and series have been published involving use of the SILC technique for sigmoid resection [3,7,[31][32][33][34][35][36][37][38], the largest of which included 10 consecutive patients who underwent resection for recurrent diverticulitis [38]. These reports concluded that SILC was safe and feasible without increased operative time, risk of complication, or prolonged hospitalization when performed by an experienced laparoscopic surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with open surgery, MLS has been associated with less pain, a quicker recovery of gastrointestinal function, improved pulmonary function, shorter hospital stays and a better postoperative quality of life (3). In addition, single-incision laparoscopic surgery (SLS) has been successfully introduced for colon cancer treatment (4)(5)(6)(7)(8), and has become a more commonly used surgical option.…”
Section: Introductionmentioning
confidence: 99%
“…There are more data, which are somewhat more reliable regarding other less complex leftsided procedures, such as left hemicolectomy or sigmoidectomy [52,[58][59][60]. In fact, sigmoidectomy is the most frequent procedure performed for benign left-side pathology, predominantly diverticular disease or large colonic polyps not suitable for endoscopic removal.…”
Section: Feasibility and Safety Of Single-incision Colectomymentioning
confidence: 99%